Health-related quality of life in long-term disease-free breast cancer survivors versus female population controls in Germany - Doege, Daniela; Brenner, Hermann; Arndt, Volker (Breast cancer research and treatment, 2019)
Purpose: Little is known about breast cancer (BC) survivors’ health-related quality of life (HRQoL) > 5 or even > 10 years past diagnosis. It is of interest whether, in the long run, survivors’ HRQoL aligns with that of the general population. Study objectives were to (1) compare disease-free BC survivors’ HRQoL to that of non-cancer controls, and (2) compare long-term survivors (LTS, 5-9 years post-diagnosis), very long-term survivors (VLTS, ≥ 10 years post-diagnosis), and controls with respect to their HRQoL. Methods: The samples of 2647 disease-free BC survivors (5-16 years post-diagnosis) and 1005 population controls were recruited in German multi-regional population-based studies. HRQoL was assessed by the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire—Core 30 (EORTC QLQ-C30). Differences in HRQoL were assessed with multiple regression, controlling for age and education. Results: Disease-free BC survivors < 80 years (at survey) reported overall global health status/quality of life comparable to controls, but statistically significant lower physical, role, emotional, social, and cognitive functioning. They also indicated more fatigue, insomnia, dyspnoea, and financial difficulties. However, differences were only of trivial or small clinical relevance. At age 80-89, no differences between BC survivors and controls were observed. Deficits in emotional and cognitive functioning and some symptoms (e.g. insomnia and fatigue) persist, as both LTS and VLTS reported more detriments than controls. Conclusions: In view of the persistent, small but significant detriments in disease-free BC survivors’ cognitive and emotional functioning and higher symptom burden, possibilities to prevent detriments from becoming chronic should be explored.